Extraction of medium chain triglycirides (MCTs) rich oil from flesh coconut using supercritical fluid carbon dioxide - Muhammad Naim Rozak, 1990-, author; Mohd. Azizi Che Yunus, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper Sarjana Muda Kejuruteraan (Kimia) - Universiti Teknologi Malaysia, 2013